2021
DOI: 10.1177/22779752211017275
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Conversations About High Engagement Sports Team Brands

Abstract: This study conducts an analysis of social media discussions related to high engagement sports brands. More specifically, our study examined the English Premier League (EPL); it sought to retrieve data systematically over the same day, weekly, for a period of five months. After this process, we had built 20 datasets and NodeXL was utilized to analyse the data. After we had this data, we were able to use qualitative observations to identify key users and conversations that formed around the EPL as well as the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 75 publications
(71 reference statements)
1
6
0
Order By: Relevance
“…These findings add to the body of research that has examined the role and potentials of eWOM (Srivastava et al, 2021) and the social media echo-chamber effect from a non-marketing and non-business-related perspective (Wang & Song, 2020). Our findings are also comparable to Chadwick et al (2021), who found that the Twitter account of a high impact brand (EPL) containing several distinct opinion leaders can lead to the development of a unique amplified network. Another relevant study by Guzmán et al (2021) examined tweets that were collected during Manchester United’s matchdays.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…These findings add to the body of research that has examined the role and potentials of eWOM (Srivastava et al, 2021) and the social media echo-chamber effect from a non-marketing and non-business-related perspective (Wang & Song, 2020). Our findings are also comparable to Chadwick et al (2021), who found that the Twitter account of a high impact brand (EPL) containing several distinct opinion leaders can lead to the development of a unique amplified network. Another relevant study by Guzmán et al (2021) examined tweets that were collected during Manchester United’s matchdays.…”
Section: Discussionsupporting
confidence: 90%
“…The interest in the promotional actions of influencers and the responses to such content to achieve viral status is shared by these studies. Identifying viral marketing campaigns requires a detailed analysis of three distinct elements: the influencer, the brand and the followers (Chadwick et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations